PENGEMBANGAN LKPD INTERAKTIF MENGGUUNAKAN LIVEWORKSHEET BERBASIS PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA MATERI PERSAMAAN TRIGONOMETRI UNTUK KELAS XI SMA - Fanny Elvi Mutiara Amri (Jurnal Edukasi dan Penelitian Matematika, 2022)
The learning process can run effectively and efficient if using teaching materials that are in accordance with the needs of students, support the competencies to be achieved and have a sustematic description of the material, and can facilitate students to actively from their own understanding. But in reality students still tend to be passive in learning and are not accustomed to constructing their own knowledge. The teaching materials used are printed books from erlangga and LKPD from publishers. The absence of LKPD development from educators is due to the limitations of educators in utilizing technology and time constraints in designing attractive LKPD. This resulted in the absence of a valid and practical LKPD. This study aims to create an LKPD based on a valid an Realistic Mathematics Education (RME) teaching methide, for grade XI hight school students. This type of study is a design study using the plomp development model, which includes needs analysis, program analysis, concept analysis, and student analysis. The prototyping phase consists of steps taken in the design of the LKPD. In step 1 of the prototype, a process of self-assessment is performed (self-evaluation). In prototype 2, an expert review was performed, which was then assessed by the experts to obtain a valid prototype. In phase 3 of the prototype, an individual assessment was performed by testing LKPD on 3 students with heterogeneous qualifications. During prototype 4 phase, a small group evaluation was conducted on six students with heterogeneous ability levels, to determine the practicality of the LKPD. From the studies that have been done, it os known that the LKPD based on the Realistic Mathematics Education (RME) approach on trigonometric equation material has a validity level of 86,5% with very valid criteria (based on three experts, namely teo mathematics lectures and one educator). LKPD also has a level of practicality. Using the very practical category as much as 88,38% by students in the one-to-one evaluation stage and 91,86% of the students in the small group assessment phase. Keywords – LKPD, Realistic Mathematics Education, valid, practical